(3GdhUhd Edi GdShd aj fXe SjQI GdQShd (B((3dGHf gTGe(B)s - (3eLghds; (3GHf gTGe , YHO Gdedc Hf gTGe Hf GjhH GdMejQj GdeYGaQj, LeGd GdOjf CHh eMeO,J (B213 (3g` s
(3ChdgG (B:s
(3CeG HYO , aEfi hbaJ Ydi GdSjQI GdfHhjI GdJi fXegG aJM Hf ehSi GdeZQHi fKQkG hfXekG VefgG CMGOjK fHhjI hGSJTgGOGJ aMPaJ efKhQg hGMGOjKg hPcQJ fXeg NGUI s
(3BNQgG (B:s
(3hcGf QShd Gddg jghi UdGJg Edi GdcYHg GdYXei hjQLh hjhJQ s
(3SjQI QShd Gddg Udi Gdg Ydjg hSde GdeSeGg HSjQI GHf gTGes
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs